Theory building for Ulul Albab teachers' professional development program using grounded theory method - Alwi, Nor Hayati; Abdul Manaf, Umi Kalthom; Abdul Kadir, Suhaida; Mohd Fakhruddin, Fathiyah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Developing holistic and balanced students based on the firm belief and devotion to God is the essence of Malaysia National Philosophy of Education (NPE). Many efforts have been carried out by the Ministry of Education to achieve the mission of the NPE and one of those efforts is the implementation of a program called Ulul Albab implemented in several schools in Malaysia. The existence of Ulul Albab program is rather a new phenomenon in Malaysia educational system. Not much is known about the program in terms of its development, implementation and evaluation. Only two evaluation researches on the program were found. Among important findings from the evaluation is that the program requires teachers of certain qualities (Umi Kalthom, Ady Hameme, Hafizah, Fadzilah, Nurul Fitriah, 2014). However, there was no research found that studied on Ulul Albab teachers’ quality in general and their professional development curriculum/program in specific. Thus, it is important to look into this issue since teacher is one of the key factors which contribute to students’ holistic development based on the firm belief and devotion to Allah s.w.t (Nor Hayati, 2002, 2005). The aim of this paper is to discuss the efforts on building a curriculum theory which would act as a guideline in designing a Professional Development Curriculum/Program for Ulul Albab Teachers’ in Malaysia Secondary Schools. This effort is identified as theory building or theory construction which will be carried out with the use of grounded theory research method.